The antimicrobial activity and chemical composition of Elsholtzia blanda (Benth.) Benth. essential oils in Lam Dong Province, Viet Nam - Ngoc, Nguyen Van (2023)
This study aimed to assess the chemical composition of essential oils of Elsholtzia blanda (Benth.) Benth. in Lam Dong Province, Viet Nam, and evaluate their biological activities. Essential oils obtained by hydrodistillation of the aerial parts of E. blanda were analyzed by gas chromatography-mass spectrometry (GC-MS). Thirty-one constituents were identified in the oil, and the essential oil was predominantly monoterpenoid, with camphor (25.14%), camphene (22.64%), -Pinene (11.53%), and cineole (9.89%) as the four most abundant constituents. The evaluation of antimicrobial activity using the agar wells diffusion method showed that the essential oil in all concentrations was active against the Gram-positive bacteria (Staphylococcus aureus), Gram-negative bacteria (Escherichia coli), and pathogenic yeast (Candida albicans), they are most sensitive and resistant to S. aureus strain.